Systematic In Vitro Evaluation of a Library of Approved and Pharmacologically Active Compounds for the Identification of Novel Candidate Drugs for KMT2A-Rearranged Leukemia - Karsa, Mawar; Ronca, Emma; Bongers, Angelika; Mariana, Anna; Moles, Ernest; Failes, Timothy W.; Arndt, Greg M.; Cheung, Laurence C.; Kotecha, Rishi S.; Kavallaris, Maria; Haber, Michelle; Norris, Murray D.; et al. (Frontiers in Oncology, 2022)
Patients whose leukemias harbor a rearrangement of the Mixed Lineage Leukemia (MLL/KMT2A) gene have a poor prognosis, especially when the disease strikes in infants. The poor clinical outcome linked to this aggressive disease and the detrimental treatment side-effects, particularly in children, warrant the urgent development of more effective and cancer-selective therapeutics. The aim of this study was to identify novel candidate compounds that selectively target KMT2A-rearranged (KMT2A-r) leukemia cells. A library containing 3707 approved drugs and pharmacologically active compounds was screened for differential activity against KMT2A-r leukemia cell lines versus KMT2A-wild type (KMT2A-wt) leukemia cell lines, solid tumor cells and non-malignant cells by cell-based viability assays. The screen yielded SID7969543, an inhibitor of transcription factor Nuclear Receptor Subfamily 5 Group A Member 1 (NR5A1), that limited the viability of 7 out of 11 KMT2A-r leukemia cell lines including 5 out of 7 lines derived from infants, without affecting KMT2A-wt leukemia cells, solid cancer lines, non-malignant cell lines, or peripheral blood mononuclear cells from healthy controls. The compound also significantly inhibited growth of leukemia cell lines with a CALM-AF10 translocation, which defines a highly aggressive leukemia subtype that shares common underlying leukemogenic mechanisms with KMT2A-r leukemia. SID7969543 decreased KMT2A-r leukemia cell viability by inducing caspase-dependent apoptosis within hours of treatment and demonstrated synergy with established chemotherapeutics used in the treatment of high-risk leukemia. Thus, SID7969543 represents a novel candidate agent with selective activity against CALM-AF10 translocated and KMT2A-r leukemias that warrants further investigation.